Composite hydrogel dressing for promoting wound healing, preparation and application
By loading silver ion and/or copper ion modified metal organic frame materials into hydrogels with oxidized dextran and gelatin, a composite hydrogel dressing with antibacterial, anti-biofilm and antioxidant functions was developed, which solved the problem of bacterial infection wound healing and achieved efficient antibacterial and anti-inflammatory effects.
Patent Information
- Application Number
- CN202411983390.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-03-04
AI Technical Summary
The prior art is difficult to effectively solve the problem of wound healing caused by bacterial infection, especially bacterial resistance and biofilm formation caused by antibiotic abuse. The existing hydrogel dressings lack antibacterial properties, insufficient mechanical strength and poor adhesion.
A composite hydrogel dressing is developed to load silver ion and/or copper ion-modified metal organic frame material into a hydrogel formed by oxidized dextran and gelatin. The supported MOF-Ag has antibacterial and anti-biofilm effects, and the supported MOF-Cu has antioxidant activity and can remove excess reactive oxygen.
The composite hydrogel dressing has good biocompatibility, appropriate mechanical properties and bioadhesion, stable rheology, excellent antibacterial and anti-inflammatory functions and certain hemostatic functions, and can effectively promote wound healing.
Smart Images

Figure CN119548665A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of biomedicine, and in particular relates to a composite hydrogel dressing for promoting wound healing, and its preparation and application. Background Art
[0002] Bacterial infections pose a major threat to global public health security. According to statistics, in 2019, there were 7.7 million deaths related to bacterial infections, accounting for 13.6% of the total number of deaths worldwide. More than half of bacterial infection-related deaths were caused by five bacterial pathogens: Staphylococcus aureus, Escherichia coli, Streptococcus pneumoniae, Klebsiella pneumoniae, and Pseudomonas aeruginosa. Among them, open wounds are produced after the skin is damaged. The exposed wound surface is very susceptible to bacterial infection. The bacteria continue to proliferate and release toxins, invading and damaging the damaged skin tissue. When the bacterial infection in the wound cannot be eliminated in time, the accumulation of excessive reactive oxygen species (ROS) causes oxidative damage to normal cells and causes a persistent inflammatory response. A variety of problems caused by bacterial colonization, including bacterial virulence and persistent inflammation, hinder the process of wound healing, which may turn the wound into a chronic wound that is difficult to heal, and even induce more serious complications such as sepsis.
[0003] At present, the most widely used treatment for bacterial infectious diseases in clinical practice is antibiotics, which can kill pathogens or inhibit their growth by destroying cell membrane or cell wall formation, protein synthesis or DNA replication. However, the long-term abuse of antibiotics has promoted a sharp increase in bacterial resistance. In addition, bacteria usually form biofilms during their growth. Bacterial biofilms are bacterial clusters with the protection of extracellular polymeric substances (EPS), which enable bacteria to tolerate environmental stress. Due to incomplete penetration of antibiotics, bacteria that form biofilms show enhanced resistance, and the therapeutic effect of antibiotics used clinically is poor.
[0004] Therefore, in order to cope with the antibacterial challenges of drug resistance and biofilm, it is of great significance to develop antibacterial agents that can replace antibiotics. In recent years, a variety of antibacterial nanomaterials have been developed, including metal nanoparticles, metal oxides, metal organic framework materials (MOFs), carbon-based nanomaterials, silicon-based nanomaterials and polymer nanomaterials. However, antibacterial nanomaterials have the following shortcomings: the bactericidal effect is not strong at low concentrations; they only have a single antibacterial function and cannot solve the problem of excessive inflammatory response in infected wounds; the administration method is mostly direct dripping of the solution, the solution is easy to lose, and the residence time at the site of action is short. These drawbacks limit the practical application of antibacterial nanomaterials. Based on this, it is necessary to develop nanomaterials with high-efficiency antibacterial effects and antioxidant and anti-inflammatory effects, and load them in wound dressings for local administration, so as to achieve a synergistic therapeutic effect of effective antibacterial and relieving inflammation, and promote the healing of infected wounds.
[0005] Hydrogel is a classic wound dressing, which is a three-dimensional porous network formed by physical or chemical crosslinking of polymers. Hydrogel has excellent hydrophilicity and biocompatibility. It acts as a physical barrier to close wounds and provide protection for the wound surface. It can also effectively absorb wound exudate and is suitable for the healing of damaged skin. Existing hydrogels have the following shortcomings: lack of suitable adhesion and easy detachment in active parts of the body; poor antibacterial properties and cannot meet the needs of treating bacterial infections; insufficient mechanical strength, the hydrogel is destroyed under local pressure and loses its protective ability. Therefore, it is necessary to develop composite hydrogels with suitable bioadhesion, sufficient mechanical properties, and good antibacterial and antioxidant effects to meet complex clinical treatment needs. Summary of the invention
[0006] The purpose of the present invention is to overcome the problems of bacterial invasion and persistent inflammation in wounds. The present invention provides a composite hydrogel with antibacterial and / or antioxidant functions. A metal organic framework material modified with silver ions and / or copper ions is loaded into a hydrogel formed by oxidized dextran and gelatin. The loaded MOF-Ag has antibacterial and anti-biofilm effects on Staphylococcus aureus and Escherichia coli, and the loaded MOF-Cu has superoxide dismutase-like and glutathione peroxidase-like activities, can remove excessive reactive oxygen and relieve inflammatory reactions; the obtained hydrogel has good biocompatibility, appropriate mechanical properties and bioadhesion, stable rheological properties, excellent antibacterial and anti-inflammatory functions and certain hemostatic functions.
[0007] According to a first aspect of the present invention, a method for preparing a composite hydrogel dressing for promoting wound healing is provided, wherein oxidized dextran is dissolved in deionized water to obtain an oxidized dextran solution, a metal-organic framework material modified by silver ions and / or a metal-organic framework material modified by copper ions is added to the oxidized dextran solution, and then a gelatin solution is added, and the amino groups in the gelatin undergo a Schiff base cross-linking reaction with the aldehyde groups of the oxidized dextran to obtain a gel, and at the same time, the metal-organic framework material modified by silver ions and / or the metal-organic framework material modified by copper ions is loaded onto the gel to obtain a composite hydrogel dressing.
[0008] Preferably, the preparation of the oxidized dextran is specifically as follows: a dextran aqueous solution and a sodium periodate aqueous solution are mixed to oxidize the dextran, and then the mixed solution is transferred to a dialysis bag, and dialysis is performed using deionized water as a dialysis external fluid. After the dialysis is completed, the dialysis internal fluid is taken out and freeze-dried to obtain the oxidized dextran.
[0009] Preferably, the preparation of the silver ion modified metal organic framework material comprises the following steps:
[0010] (1) dissolving zirconium tetrachloride and 2,2′-bipyridine-5,5′-dicarboxylic acid in N,N-dimethylformamide, then adding glacial acetic acid, and mixing thoroughly to obtain a mixed solution, then heating the mixed solution, centrifuging and collecting and washing the precipitate to obtain a metal organic framework compound;
[0011] (2) dispersing the metal organic framework compound obtained in step (1) in deionized water, then adding it to a silver nitrate solution for incubation, and collecting the precipitate by centrifugation to obtain a silver ion modified metal organic framework material.
[0012] Preferably, the preparation of the copper ion modified metal organic framework material comprises the following steps:
[0013] (1) dissolving zirconium tetrachloride and 2,2′-bipyridine-5,5′-dicarboxylic acid in N,N-dimethylformamide, then adding glacial acetic acid, and mixing thoroughly to obtain a mixed solution, then heating the mixed solution, centrifuging and collecting and washing the precipitate to obtain a metal organic framework compound;
[0014] (2) dispersing the metal organic framework compound obtained in step (1) in deionized water, then adding it to a copper nitrate solution for incubation, and collecting the precipitate by centrifugation to obtain a copper ion modified metal organic framework material.
[0015] According to another aspect of the present invention, a prepared composite hydrogel dressing is provided.
[0016] According to another aspect of the present invention, there is provided use of the composite hydrogel dressing in preparing a material for promoting wound healing.
[0017] Preferably, the wound is a diabetic foot wound, a bacterially infected wound or a burn wound.
[0018] Preferably, when the composite hydrogel dressing contains a metal organic framework material modified with silver ions, the composite hydrogel dressing has antibacterial and anti-biofilm effects on Staphylococcus aureus and / or Escherichia coli.
[0019] Preferably, when the composite hydrogel dressing contains a copper ion-modified metal organic framework material, the composite hydrogel dressing has superoxide dismutase-like and glutathione peroxidase-like activities and can remove excess reactive oxygen species.
[0020] In general, the above technical solution conceived by the present invention has the following technical advantages compared with the prior art:
[0021] (1) The present invention prepares a hydrogel dressing for promoting wound healing that has both a silver ion-modified metal organic framework material and a copper ion-modified metal organic framework material. The hydrogel dressing has two strategies for promoting wound healing. First, the hydrogel has antibacterial and anti-biofilm effects on Staphylococcus aureus and Escherichia coli, and can eliminate bacterial infection at the wound. Second, the hydrogel has superoxide dismutase-like and glutathione peroxidase-like activities, and can remove excess reactive oxygen and relieve inflammatory reactions, and has application prospects in treating bacterially infected wounds.
[0022] (2) The present invention loads silver ion-modified metal organic framework materials and / or copper ion-modified metal organic framework materials into a hydrogel formed by oxidized dextran and gelatin. The loaded MOF-Ag has antibacterial and anti-biofilm effects (antibacterial effects) on Staphylococcus aureus and Escherichia coli, and the loaded MOF-Cu has superoxide dismutase-like and glutathione peroxidase-like activities (anti-inflammatory effects), which can remove excessive reactive oxygen and relieve inflammatory reactions. By loading nanomaterials in hydrogels through simple steps, the loading components can be changed according to actual needs to obtain hydrogels with antibacterial and / or anti-inflammatory functions.
[0023] (3) The hydrogel prepared by the present invention has good adhesion and can fit the wound (the hydrogel can adhere to objects of different materials, and the hydrogel can deform with the movement of the finger joints without falling off from the moving parts). In addition, the hydrogel has stable rheological properties (rheological results show that the hydrogel maintains stable rheological properties and a stable structure under different oscillation frequencies and pressures), which meets the needs of practical use.
[0024] (4) The hydrogel prepared by the present invention has good morphology, is easy to use, has good biocompatibility and a certain hemostatic function (the hydrogel reduced the amount of bleeding in both the mouse tail bleeding and liver bleeding models), and has the potential to be used as a wound dressing.
[0025] (5) The hydrogel preparation method prepared by the present invention is simple to operate, has low economic cost, high repeatability, and is capable of industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The morphology characterization of MOF-Ag and MOF-Cu in Example 4, a is the transmission electron microscope image and element mapping image of MOF-Ag, and b is the transmission electron microscope image and element mapping image of MOF-Cu.
[0027] Figure 2 These are the characterization results of the hydrogel in Example 5, where a is an appearance image of the hydrogel gelation process, b is a plasticity graph, c is an injectability graph, d is an adhesion graph, e is a scanning electron microscope graph, f is a swelling graph, and gh is a rheology graph.
[0028] Figure 3 The results of the antibacterial plate experiments on Escherichia coli and Staphylococcus aureus of MOF-Ag, MOF-Cu, OG (hydrogel prepared from oxidized dextran and gelatin), OGA (hydrogel prepared from MOF-Ag, oxidized dextran and gelatin), OGC (hydrogel prepared from MOF-Cu, oxidized dextran and gelatin) and OGAC (hydrogel prepared from MOF-Ag, MOF-Cu, oxidized dextran and gelatin) in Example 6. a is an image of Escherichia coli colonies on LB agar plates, and b is an image of Staphylococcus aureus colonies on LB agar plates.
[0029] Figure 4 The results of the anti-biofilm ability of MOF-Ag, MOF-Cu, OG and OGAC against Staphylococcus aureus and Escherichia coli in Example 7. a is the crystal violet staining result of inhibiting the formation of Escherichia coli biofilm, b is the crystal violet staining result of destroying the mature biofilm of Escherichia coli, c is the crystal violet staining result of inhibiting the formation of Staphylococcus aureus biofilm, and d is the crystal violet staining result of destroying the mature biofilm of Staphylococcus aureus.
[0030] Figure 5 The results of the fluorescence imaging of OGAC against Staphylococcus aureus and Escherichia coli in Example 8 are shown in Figure 8. a is the result of the biofilm formation inhibition experiment, and b is the result of the mature biofilm destruction experiment.
[0031] Figure 6 The results of the evaluation of superoxide dismutase-like and glutathione peroxidase-like activities of MOF-Ag, MOF-Cu, OG, OGA, OGC and OGAC in Example 9 are shown in Table 1. ac is the result of the evaluation of superoxide dismutase-like activity, and df is the result of the evaluation of glutathione peroxidase-like activity.
[0032] Figure 7 The cytotoxicity of MOF-Ag, MOF-Cu, OG, OGA, OGC and OGAC in Example 10.
[0033] Figure 8 The in vivo hemostatic effect of OGAC in Example 11. a is the hemostatic result of the mouse tail bleeding model, and b is the hemostatic result of the liver bleeding model.
[0034] Fig. 9The hydrogel in Example 12 is a schematic diagram of the hydrogel strategy for treating wounds infected with Staphylococcus aureus, b is wound pictures of mice in different groups on days 0, 3, 7, and 10, c is a quantitative statistical graph of the corresponding relative wound area, d is the body weight of mice in different groups on days 0, 3, 7, and 10, e is an overlay of wound marks during wound healing in mice in different groups, and fh are H&E staining, Masson staining, and immunohistochemical staining of Ki67 on skin tissue on day 10.
[0035] Fig.10 The results of the evaluation of the anti-infection ability of the hydrogel on infected wounds of mice in Example 12 are shown in Figure 12. a is a colony photo of wound tissues of different groups on the LB agar plate on the first day, and b is a quantitative statistical graph of the corresponding bacterial survival rate.
[0036] Fig.11 The results of the evaluation of the anti-inflammatory and angiogenic abilities of the hydrogel on infected wounds of mice in Example 12 are shown in Figure 12. af are the qRT-PCR analysis results of IL-1β, iNOS, MMP-9, Mrc1, Arg-1 and VEGF in wound tissues of different groups on the 7th day, gh are the quantitative statistics of immunofluorescence staining of CD86 and CD206 in wound tissues of different groups on the 7th day, and ik are the immunofluorescence staining images of CD86, CD206 and CD31 in wound tissues of different groups on the 7th day. DETAILED DESCRIPTION
[0037] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0038] Example 1
[0039] The present invention provides a method for preparing a silver ion-modified metal organic framework material, and the specific preparation steps are as follows:
[0040] (1) Dissolve 0.23 g of zirconium tetrachloride and 0.24 g of 2,2′-bipyridine-5,5′-dicarboxylic acid in 100 mL of N,N-dimethylformamide, then add 4.65 mL of glacial acetic acid, ultrasonically treat for 2 min, and mix well. The mixed solution is reacted at 120°C for 18 h, cooled to room temperature, and centrifuged to collect and wash the precipitate (9500 rpm, 5 min). The MOF precipitate is washed 1-2 times with N,N-dimethylformamide, tetrahydrofuran, ethanol, and deionized water in sequence. The white solid finally obtained is a metal organic framework compound, abbreviated as MOF, which is dispersed in ethanol for storage.
[0041] (2) The prepared MOF was centrifuged (9500 rpm, 5 min) and then redispersed in deionized water. 5 mg of MOF was added to 5 mL of 0.1 mM silver nitrate solution, incubated on a rotary shaker for 12 h, and then the precipitate was collected by centrifugation and washed three times with deionized water to obtain a silver ion-modified metal organic framework material, abbreviated as MOF-Ag.
[0042] Example 2
[0043] The present invention provides a method for preparing a copper ion-modified metal organic framework material, and the specific preparation steps are as follows:
[0044] (1) Dissolve 0.23 g of zirconium tetrachloride and 0.24 g of 2,2′-bipyridine-5,5′-dicarboxylic acid in 100 mL of N,N-dimethylformamide, then add 4.65 mL of glacial acetic acid, ultrasonically treat for 2 min, and mix well. The mixed solution is reacted at 120°C for 18 h, cooled to room temperature, and centrifuged to collect and wash the precipitate (9500 rpm, 5 min). The MOF precipitate is washed 1-2 times with N,N-dimethylformamide, tetrahydrofuran, ethanol, and deionized water in sequence. The white solid finally obtained is a metal organic framework compound, abbreviated as MOF, which is dispersed in ethanol for storage.
[0045] (2) The prepared MOF was centrifuged (9500 rpm, 5 min) and then redispersed in deionized water. Each 5 mg of MOF was added to 5 mL of 0.05 mM copper nitrate trihydrate solution, incubated on a rotary shaker for 12 h, and then the precipitate was collected by centrifugation and washed three times with deionized water to obtain a copper ion modified metal organic framework material, abbreviated as MOF-Cu.
[0046] Example 3
[0047] The present invention provides a hydrogel dressing for promoting the healing of bacterially infected wounds, and the specific preparation steps are as follows:
[0048] (1) 2 g of dextran and 1.98 g of sodium periodate were added to 25 mL of deionized water, respectively. The two solutions were mixed after ultrasonic dissolution. After stirring at room temperature in the dark for 24 h, 800 μL of ethylene glycol was added and stirred for 30 min to terminate the reaction. The average molecular weight of dextran was 70,000.
[0049] (2) The mixed solution after the reaction was transferred to a dialysis bag with a molecular cutoff of 3500Da, and after dialysis for 3 days with deionized water as the dialysis external fluid, the dialysis internal fluid was taken out and freeze-dried to obtain a white solid, which was oxidized dextran (Odex); the freeze-drying step was to divide the dialysis internal fluid into 5mL centrifuge tubes at a volume of 500μL per tube, freeze at -80°C for 12h, and freeze-dry for 12h;
[0050] (3) Dissolve Odex in deionized water to prepare 0.8% (w / v), 1.4% (w / v) and 2.0% (w / v) Odex solutions, and dissolve gelatin (Gel) in deionized water to prepare 16% (w / v) Gel solution;
[0051] (4) The Odex in step (5) was fully mixed with a 16% (w / v) Gel solution at a ratio of 1:1 (v / v) at 37° C., and allowed to stand to obtain a hydrogel, which was named OG. According to the mass volume percentage concentration of Odex before mixing with the hydrogel precursor solution, it was recorded as OG-0.8, OG-1.4, and OG-2.0;
[0052] (5) As a control group, MOF-Ag was dispersed in a 1.4% (w / v) Odex solution, and then mixed with an equal volume of a 16% (w / v) Gel solution at 37°C, and allowed to stand to obtain a composite hydrogel named OGA, wherein the antibacterial hydrogel contained 100 μg / mL of MOF-Ag. As a control group, MOF-Cu was dispersed in a 1.4% (w / v) Odex solution, and then mixed with an equal volume of a 16% (w / v) Gel solution at 37°C, and allowed to stand to obtain a composite hydrogel named OGA, wherein the antibacterial hydrogel contained 200 μg / mL of MOF-Cu.
[0053] (6) MOF-Ag and MOF-Cu were dispersed in 1.4% (w / v) Odex solution, and then mixed with 16% (w / v) Gel solution at 37°C in equal volumes, and allowed to stand to obtain a composite hydrogel named OGAC. Preferably, OGAC contains 100 μg / mL MOF-Ag and 200 μg / mL MOF-Cu.
[0054] Example 4
[0055] In order to prove the successful preparation of MOF-Ag and MOF-Cu in Example 1 and Example 2, the appearance of MOF-Ag and MOF-Cu was observed using a scanning electron microscope. Figure 1 shown.
[0056] Depend on Figure 1 It can be seen that both MOF-Ag and MOF-Cu present similar octahedral morphology, uniform size, and particle size range of 150-200nm, which proves that MOF-Ag and MOF-Cu are successfully prepared.
[0057] Example 5
[0058] In order to demonstrate the feasibility of applying the hydrogel prepared in Example 3 to wound healing, the present invention conducted a series of characterizations on the OGAC hydrogel prepared in Example 1 (including the OG hydrogel prepared by adjusting the preparation conditions). The specific results are shown in Figure 2 .
[0059] Figure 2 Figure a is an image illustration of the hydrogel preparation process. MOF-Ag and MOF-Cu are dispersed in the oxidized dextran solution, and then the gelatin solution is added and mixed evenly. The mixed solution appears light blue and forms a hydrogel after standing at room temperature. Figure 2 b in the figure is a hydrogel with a specific shape prepared by injecting the hydrogel precursor solution into a mold, which proves that the hydrogel has plasticity. Figure 2 In figure c, the hydrogel precursor solution is loaded into a syringe, and a hydrogel with the word "HUST" can be formed in situ by injection, proving that the hydrogel can be injected. Figure 2 The hydrogel in figure d can fit on the fingers, and when the fingers are bent at different angles, the hydrogel can keep fitting and does not fall off with the movement of the fingers. The hydrogel also has adhesion to objects of different materials, proving that the hydrogel has good adhesion properties. Figure 2 In Fig. e, the microstructure of OG and OGAC is a uniform macroporous network structure with pore sizes ranging from 100 μm to 200 μm. Figure 2 The hydrogels containing different oxidized dextran in f all swelled in the solution over time, proving that the hydrogels have good swelling properties and can absorb water and wound exudate. Figure 2 The hydrogels containing different oxidized dextran in the gh maintained stable storage modulus and loss modulus in the oscillation frequency of 0.1Hz to 10Hz and the deformation range of 0.5% to 300%, proving that the hydrogels have stable rheological properties and stable structure.
[0060] Example 6
[0061] The present invention investigates the antibacterial activity of MOF-Ag, MOF-Cu, OG, OGA, OGC and OGAC against Staphylococcus aureus and Escherichia coli. The specific steps of the antibacterial experiment are as follows: the bacteria are cultured in liquid Luria-Bertani (LB) medium at 37°C until the exponential growth phase, and then diluted to 10 with HEPES (10 mM, pH = 7.4). 6 CFU / mL. 10μg / mL MOF-Ag, 100μg / mL MOF-Cu, 100μL OG and 100μL OGAC were added to 800μL bacterial suspension and cultured at 37℃ for 4h. Then, the diluted bacterial suspension of each group was spread on a solid LB agar plate and cultured at 37℃ for 18h, and the number of colonies was calculated. The antibacterial test results are shown in Figure 3 shown.
[0062] exist Figure 3 In the experiment, bacteria incubated with 100μg / mL MOF-Cu grew normally. In contrast, when the MOF-Ag concentration was 10μg / mL, there was almost no growth of Escherichia coli or Staphylococcus aureus colonies in the culture dish, indicating that MOF-Ag has excellent antibacterial activity at low concentrations and MOF-Cu has poor antibacterial effect. Bacteria incubated with OG and OGC grew normally, proving that hydrogels without antibacterial agents and hydrogels loaded with MOF-Cu do not have antibacterial effects. After the bacteria were incubated with OGAC, there was almost no colony growth in the culture dish, proving that OGAC has excellent antibacterial activity.
[0063] Example 7
[0064] The present invention investigates the anti-biofilm ability of MOF-Ag, MOF-Cu, OG and OGAC against Staphylococcus aureus and Escherichia coli. The specific steps of the anti-biofilm crystal violet staining experiment are as follows: the bacteria are incubated in liquid LB medium (10 6 CFU / mL) and the formed biofilm was used as the control group. For the experiment of inhibiting biofilm formation, MOF-Ag, MOF-Cu, OG and OGAC were added to the bacterial suspension and cultured for 24 hours. For the experiment of destroying mature biofilm, MOF-Ag, MOF-Cu, OG and OGAC were added to the mature biofilm and cultured for 24 hours. All biofilms were washed with HEPES (10mM, pH=7.4), and then stained with 0.1% CV solution for 20 minutes. After removing the staining solution, rinsed three times with HEPES, and the stained biofilm was dissolved with 200μL 95% ethanol. The absorbance of all groups at 570nm was measured, and the ratio of the residual biofilm amount in each group to the biofilm amount in the control group was calculated. The experimental results are shown in the figure Figure 4 shown.
[0065] Depend on Figure 4 It can be seen that the same anti-biofilm effect trend exists in the anti-biofilm results of Staphylococcus aureus and Escherichia coli: the relative amount of biofilm in the MOF-Cu and OG groups is close to that in the control group, and the relative amount of biofilm in the MOF-Ag and OGAC groups is significantly reduced, and the biofilm is destroyed. The results show that MOF-Cu and OG do not have anti-biofilm ability, and MOF-Ag and OGAC can inhibit biofilm formation and destroy mature biofilms.
[0066] Example 8
[0067] The present invention conducted fluorescence imaging observation on the anti-biofilm ability of OGAC against Staphylococcus aureus and Escherichia coli. The specific steps of anti-biofilm fluorescence imaging are as follows: the bacteria are placed in liquid LB medium (10 6 CFU / mL) culture, and the formed biofilm was used as the control group. For the biofilm formation inhibition experiment, OGAC was co-cultured with the bacterial suspension for 24 hours. For the mature biofilm destruction experiment, OGAC was co-cultured with the mature biofilm for 24 hours. Subsequently, all biofilms were washed with HEPES (10mM, pH=7.4) and stained with fluorescein diacetate (FDA) and propidium iodide (PI) for 30 minutes at 37°C in the dark. After washing twice, the biofilm was imaged using a confocal laser scanning microscope (CLSM). The experimental results are shown in Figure 5 shown.
[0068] exist Figure 5 In a, after the bacterial suspension was incubated with OGAC, the bacteria were killed and failed to form a biofilm, which consisted of mostly dead bacteria with red fluorescence and a small number of live bacteria with green fluorescence. Figure 5 In b, the mature biofilm treated with OGAC showed mainly red fluorescence after staining, indicating that there were a large number of dead bacteria and the mature biofilm was destroyed. The results showed that OGAC can effectively inhibit the formation of biofilm and remove mature biofilm.
[0069] Example 9
[0070] The present invention investigates the superoxide dismutase-like and glutathione peroxidase-like activities of MOF-Ag, MOF-Cu, OG, OGA, OGC and OGAC. The nitro blue tetrazolium (NBT) experiment is used to evaluate the superoxide dismutase-like activity, and the specific steps are: 130mM methionine (Met), 20μM riboflavin, 100μM 4.5mM nitro blue tetrazolium (NBT) and 100μM disodium ethylenediaminetetraacetate (EDTA-2Na) are added to Tris-HCl buffer (0.1M, pH 7.6). MOF-Ag, MOF-Cu, OG and OGAC are added to the above-mentioned mixed solution respectively. Then, each group of samples is irradiated with white light for 10 minutes, and the absorbance of the mixed solution at 620nm after the reaction is measured. The GPx detection kit was used to evaluate the glutathione peroxidase-like activity of MOF-Ag, MOF-Cu, OG, OGA, OGC and OGAC. The experiment was carried out according to the instructions of the kit. Figure 6 shown.
[0071] Superoxide dismutase and glutathione peroxidase are important natural antioxidants in the body, which can remove strong oxidizing substances to protect cells. Superoxide dismutase can remove superoxide anion free radicals (O2 ·- ), reducing the excess O2 ·- the damage caused. Figure 6 In a, with the increase of MOF-Cu concentration, O2 ·- The removal rate gradually increased. When the MOF-Cu concentration was 20 μg / mL, O2 ·- The clearance rate reached 95.5%. Figure 6 In panel b, the absorbance at 620 nm of the MOF-Ag group was not significantly different from that of the control group. Figure 6 OG and OGA group O2 ·- The clearance rate was low, and there was a significant difference in O2 between the OGC and OGAC groups. ·- The experimental results show that MOF-Cu and OGAC have excellent superoxide dismutase-like activity.
[0072] Glutathione peroxidase-like enzymes can scavenge hydrogen peroxide. Figure 6 In (d), the glutathione peroxidase-like activity of MOF-Cu increased with its concentration, and the enzyme activity reached the maximum at 50 μg / mL. Figure 6 In Figure 4, the absorbance of MOF-Ag at 412 nm was not significantly different from that of the control group. Figure 6The glutathione peroxidase activity in the OG and OGA groups was low, while that in the OGC and OGAC groups was significantly higher. The experimental results show that MOF-Cu and OGAC have excellent glutathione peroxidase activity.
[0073] Example 10
[0074] The present invention investigated the cytotoxicity of MOF-Ag, MOF-Cu, OG, OGA, OGC and OGAC. The specific steps are as follows: human umbilical vein endothelial cells (HUVEC) were inoculated into a 96-well plate (10 4 cells / well) and cultured for 12 hours. Then, MOF-Ag and MOF-Cu were added to the wells at a final concentration of 40μg / mL. In addition, 20μL of OG, OGA, OGC and OGAC containing 200μg / mL MOF-Ag and 200μg / mL MOF-Cu were prepared for co-culture with cells. Untreated cells were set as the control group. After 24 hours of culture, the hydrogel was removed, the original culture medium was discarded, and a DMEM solution containing 10% (v / v) CCK-8 was added to each well. The absorbance of all groups at 450nm was measured, and the cell survival rate was calculated. The experimental results are shown in Figure 7 shown.
[0075] exist Figure 7 In the experiment, the cell viability of MOF-Cu, OG, OGA, OGC and OGAC groups was maintained above 89%, while only 47.3% of the cells in the MOF-Ag group survived. The results showed that MOF-Ag had certain cytotoxicity, but after combining it with hydrogel, the cytotoxicity of OGA and OGAC was significantly reduced. Therefore, MOF-Ag was loaded into hydrogel, and Ag in MOF-Ag + The release of Ag was hindered by the hydrogel, which reduced + The local rapid and large-scale release of OGAC significantly reduces its toxicity to normal cells. The experimental results show that OGAC has good biocompatibility.
[0076] Embodiment 11
[0077] The present invention investigates the in vivo hemostatic performance of OGAC. The specific steps are as follows: for the mouse tail bleeding model, the mouse is anesthetized with isoflurane, the mouse tail tip is cut with surgical scissors of equal length, the tail wound is immediately covered with OGAC, the blood loss is evaluated, and the mouse is killed after the experiment is completed. For the mouse liver bleeding model, the mouse is anesthetized with isoflurane, and an incision is made under the mouse chest with surgical scissors to expose the liver, and the liver is pierced with a scalpel to create a bleeding wound, and the wound is immediately covered with OGAC, the blood loss is evaluated, and the mouse is killed after the experiment is completed. The experimental results are as follows. Figure 8 shown.
[0078] Depend on Figure 8 It can be seen that in the mouse tail bleeding and liver bleeding models, the amount of bleeding in the OGAC group was significantly reduced. The results showed that OGAC effectively reduced the amount of bleeding and had a certain hemostatic ability.
[0079] Example 12
[0080] The present invention investigates the therapeutic effect of hydrogel on infected wounds in mice. The specific steps are as follows: using isoflurane to anesthetize mice, using a ring mold with an inner diameter of 8 mm as a template, making a circular skin wound with a diameter of about 8 mm on the back of each mouse, and inoculating Staphylococcus aureus (10 9 CFU / mL) was directly injected into the wound area. 30 μL of normal saline, 10 mg / mL cefquinome sulfate (CS), OG and OGAC were dripped onto the wound surface of mice in different groups. Wound photos and body weight were recorded on days 0, 3, 7 and 10 to monitor the wound healing process. The mice were killed on day 10 to obtain wound tissue for histological analysis. The experimental results are shown in Fig. 9 shown.
[0081] The anti-infection ability of the hydrogel in infected wounds of mice was evaluated. The specific steps were as follows: on the first day, the wound tissue was obtained and soaked in physiological saline, the supernatant of the sample was diluted and spread on solid LB agar medium, and then cultured at 37°C for 18 hours, and the colonies were photographed and counted. The experimental results are shown in Figure 2. Fig.10 shown.
[0082] The anti-inflammatory and angiogenic abilities of the hydrogel in infected wounds of mice were evaluated. The specific steps were as follows: skin tissue samples were obtained on the 7th day, and the expression levels of IL-1β, iNOS, MMP-9, Mrc1, Arg-1 and VEGF were detected by qRT-PCR. Immunofluorescence staining was performed for CD86 associated with M1 macrophages, CD206 associated with M2 macrophages, and CD31 associated with new blood vessels in the tissues. The experimental results are shown in Figure 2. Fig.11 shown.
[0083] Fig. 9 Figure a is a schematic diagram of the OGAC strategy for treating wounds infected with Staphylococcus aureus. Fig. 9 The wound images, area quantification results, and wound trace overlays on different days in bc and e show that the wounds in the group treated with OGAC healed faster than those in the other groups, with the most significant difference observed on day 7. On day 10, the wounds treated with OGAC were almost completely healed, with the smallest wound area (2.1%). Fig. 9 The weight of mice on different days in d is shown in Figure 4. The weight of mice in different groups remained stable, indicating that the physiological state of the mice was normal. Fig. 9Figure f is the hematoxylin-eosin (H&E) staining result of mouse wound skin tissue. Compared with other groups, the regenerated tissue structure of the skin in the OGAC treatment group was more complete, the inflammatory cell infiltration was reduced, and the blood vessels were evenly distributed. Fig. 9 (g) is the Masson staining result. Compared with other groups, the blue-stained collagen fibers in the OGAC-treated group were the most abundant and evenly arranged, indicating an increased accumulation of regenerated collagen. Fig. 9 h in the figure is the result of Ki67 immunohistochemical staining. The proportion of dark brown staining in the OG and OGAC treatment groups was greater than that in other control groups, and the Ki67 positive level was higher, indicating that cell proliferation during re-epithelialization was promoted. The results showed that OGAC contributed to collagen deposition, cell proliferation, and skin regeneration, and significantly promoted wound healing.
[0084] exist Fig.10 In a, a large number of colonies grew in the culture dishes of the saline group and the OG group, while fewer colonies grew in the culture dishes of the CS and OGAC groups. Fig.10 b in the figure is the corresponding colony count result. The results show that OGAC has effective antibacterial activity in vivo and can eliminate bacterial infection in wounds.
[0085] exist Fig.11 In the ac, the expression of genes related to pro-inflammation (IL-1β, iNOS, and MMP-9) was significantly decreased in the OGAC group compared with the other groups. Fig.11 Among the samples, genes related to anti-inflammation (Mrc1 and Arg-1) showed the highest expression levels in the OGAC group compared with the other groups. These results suggest that OGAC reduces excessive inflammatory responses in infected wounds. Fig.11 In figure f, the mRNA expression of angiogenesis-related (VEGF) in the OGAC group was significantly increased, indicating that OGAC has the potential to promote angiogenesis. Fig.11 Among the gk, the M2 macrophage-related anti-inflammatory factors CD206 and platelet endothelial cell adhesion molecule-1 (CD31) were expressed most highly in the OGAC group, while the M1 macrophage-related pro-inflammatory factor CD86 was expressed least highly in the OGAC group. The results showed that OGAC has the function of reducing inflammatory response and promoting angiogenesis.
[0086] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a composite hydrogel dressing for promoting wound healing, characterized in that: Oxidized dextran is dissolved in deionized water to obtain an oxidized dextran solution, a metal organic framework material modified by silver ions and / or a metal organic framework material modified by copper ions is added to the oxidized dextran solution, and then a gelatin solution is added, and the amino groups in the gelatin and the aldehyde groups of the oxidized dextran undergo a Schiff base cross-linking reaction to obtain a gel, and at the same time, the metal organic framework material modified by silver ions and / or the metal organic framework material modified by copper ions is loaded onto the gel to obtain a composite hydrogel dressing.
2. The method for preparing the composite hydrogel dressing for promoting wound healing according to claim 1, characterized in that: The preparation of the oxidized dextran is specifically as follows: a dextran aqueous solution and a sodium periodate aqueous solution are mixed to oxidize the dextran, and then the mixed solution is transferred to a dialysis bag, and dialysis is performed using deionized water as a dialysis external fluid. After the dialysis is completed, the dialysis internal fluid is taken out and freeze-dried to obtain the oxidized dextran.
3. The method for preparing the composite hydrogel dressing for promoting wound healing according to claim 1, characterized in that: The preparation of the silver ion modified metal organic framework material comprises the following steps: (1) dissolving zirconium tetrachloride and 2,2′-bipyridine-5,5′-dicarboxylic acid in N,N-dimethylformamide, then adding glacial acetic acid, and mixing thoroughly to obtain a mixed solution, then heating the mixed solution, centrifuging and collecting and washing the precipitate to obtain a metal organic framework compound; (2) dispersing the metal organic framework compound obtained in step (1) in deionized water, then adding it to a silver nitrate solution for incubation, and collecting the precipitate by centrifugation to obtain a silver ion modified metal organic framework material.
4. The method for preparing the composite hydrogel dressing for promoting wound healing according to claim 1, characterized in that: The preparation of the copper ion modified metal organic framework material comprises the following steps: (1) dissolving zirconium tetrachloride and 2,2′-bipyridine-5,5′-dicarboxylic acid in N,N-dimethylformamide, then adding glacial acetic acid, and mixing thoroughly to obtain a mixed solution, then heating the mixed solution, centrifuging and collecting and washing the precipitate to obtain a metal organic framework compound; (2) dispersing the metal organic framework compound obtained in step (1) in deionized water, then adding it to a copper nitrate solution for incubation, and collecting the precipitate by centrifugation to obtain a copper ion modified metal organic framework material.
5. The composite hydrogel dressing prepared by the method according to any one of claims 1 to 4.
6. Use of the composite hydrogel dressing as claimed in claim 5 in preparing a material for promoting wound healing.
7. The use according to claim 6, characterized in that The wound is a diabetic foot wound, a bacterially infected wound or a burn wound.
8. The use according to claim 6, characterized in that When the composite hydrogel dressing contains a metal organic framework material modified with silver ions, the composite hydrogel dressing has antibacterial and anti-biofilm effects on Staphylococcus aureus and / or Escherichia coli.
9. The use according to claim 6, characterized in that When the composite hydrogel dressing contains a copper ion-modified metal organic framework material, the composite hydrogel dressing has superoxide dismutase-like and glutathione peroxidase-like activities and can remove excessive active oxygen.
Citation Information
Cited By
Composite hydrogel and application thereof in preparation of diabetes wound repair dressing
CN120884735A
A composite hydrogel and its application in the preparation of a diabetic wound repair dressing
CN120884735B
Hydrogel with photothermal effect and preparation method thereof
CN121203170A
Rapid hemostatic material and application thereof
CN121668375A
Hemostatic material, hemostatic gauze and preparation method thereof
CN121668376A